A numerical solution for a class of time fractional diffusion equations with delay - Pimenov, Vladimir G.; Hendy, Ahmed S. (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes a numerical scheme for a class of fractional diffusion equations with fixed time delay. The study focuses on the uniqueness, convergence and stability of the resulting numerical solution by means of the discrete energy method.
Keywords: fractional diffusion equation with delay; difference scheme; convergence analysis